Clinical indicators that influence a clinician's decision to start L-thyroxine treatment in prematurity with transient hypothyroxinemia - Aslan Yilmaz; Yavuz Ozer; Nesrin Kaya; Aydilek Dagdeviren Cakir; Hazal Cansu Culpan; Yildiz Perk; Mehmet Vural; Olcay Evliyaoglu (BMC, 2023)
Abstract Background Transient hypothyroxinemia of prematurity (THOP) is defined as a low level of circulating thyroxine (T4), despite low or normal thyroid-stimulating hormone (TSH) levels. Aims: We aimed to evaluate the incidence of THOP, the clinical and laboratory findings of preterm infants with this condition and the levothyroxine (L-T4) treatment. Methods Preterm infants (n = 181) delivered at 24-34 weeks of gestation were evaluated by their thyroid function tests that were performed between the 10th and 20th days of postnatal life and interpreted according to the gestational age (GA) references. Clinical and laboratory characteristics of the patients with THOP and normal thyroid function tests were compared. Patients with THOP and treated with L-T4 were compared with the ones who were not regarding laboratory, and clinical characteristics. Results Incidence of hypothyroxinemia of prematurity was 45.8% (n = 83). Euthyroidism, primary hypothyroidism, and subclinical hypothyroidism were diagnosed in 47.5% (n = 86), 5% (n = 9) and 1.7% (n = 3) of the patients, respectively. Mean birth weight (BW) and GA were significantly lower in the hypothyroxinemia group than in the euthyroid group (p < 0.001). L-T4 was started in 43% (n = 36) of the patients with THOP. Treatment initiation rate was 44.4% (n = 16) in 24-27 wk, 41.6% (n = 15) in 28-30 wk, and 13.8% (n = 5) in 31-34 wk. As the GA increased, the incidence of THOP and the rate of treatment initiation decreased (p < 0.001). The lowest free thyroxine (FT4) cut-off value was 0.72 ng/dl in the treated group. In addition, incidences of vancomycin + amikacin, caffeine, dopamine treatments, RDS, IVH, BPD, central catheter, FFP transfusion, and ventilator support were higher in the treated group (P < 0.05). Conclusion This study revealed that prevalence of THOP increased as the GA and BW decreased. As the GA decreased, THOP patients requiring L-T4 treatment increased. Additionally, association with comorbid diseases increased the requirement of treatment.